(untitled) (Research, Society and Development, 2022)
Introduction: recent data show that exposure to certain conditions during pregnancy may result in the development of autism. Objective: to evaluate the nutritional status and perinatal characteristics of children with autism spectrum disorder. Methodology: A descriptive and cross-sectional study was conducted in 2021, with 47 children of both genders, with autism, in different degrees of severity, aged ≤8 years, treated at a reference center in the city of Belém, Pará. After the legal guardians signed the free and informed consent form, weight and height were collected to evaluate the nutritional status and later a form was applied to collect data on age, sex and perinatal characteristics of the children. Results: There was a significant prevalence of male gender (89.4%; n=42) and children 5 years old (40.4%; n=19). About the perinatal characteristics, it was observed that the significant majority (p<0. 05) had low birth weight (74.5%; n=35), pre-term birth (53.2%; n=25), planned cesarean type delivery (22; 46.8%), the main gestational complication was recurrent urinary tract infection (42.6%, n=20), while neonatal jaundice was the main complication among children (10.6%; n=5), 44.7% (n=21) mothers reported antibiotic use during pregnancy, and the prevalent age at conception was between 26 and 35 years for mothers (70.2%; n=33) and fathers (72.3%; n=34). In the evaluation of nutritional status, it was evident that overweight was the main nutritional alteration in this population. Conclusion: It is inferred that the maternal environment during pregnancy significantly influences neurodevelopmental changes.